Covid-19 supply chain disruptions and their consequences on the Volkswagen group - Vašíčková, Tereza; Abdallah, Kareem Issam; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The COVID-19 pandemic significantly disrupted global supply chains, challenging businesses across all sectors, including the automotive industry. This Bachelor Thesis examines the short-term and long-term impacts of these disruptions on the Volkswagen Group's strategies. It focuses on challenges such as revenue losses, increased costs, and production halts, particularly due to semiconductor shortages. The thesis also highlights Volkswagen’s financial, social, and innovative strategies to mitigate these challenges and adapt to an evolving economic landscape.
Vedoucí práce: Kareem Issam Abdallah
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses